Peran Guru dalam Perkembangan Motorik Kasar Anak Usia Dini di Era Teknologi: Tantangan dan Peluang - Sundari, Ayu; Mayar, Farida; Saputri, Elvi Helmi; Octarina, Merlyn; Herfinda, Nensi (Lembaga Yasin AlSys, 2026)
This study is motivated by the importance of developing gross motor skills in early childhood as a foundation for physical health, learning readiness, and socio-emotional development, which in the current technological era faces the challenge of increasing screen use and decreasing physical activity. The study aims to describe the role of teachers in developing gross motor skills in early childhood in the era of technology and to identify the challenges and opportunities that arise in this process. A literature study method was employed by reviewing various scientific articles, national journals, and regulations related to early childhood development. The findings indicate that teachers have a strategic role as movement facilitators, designers of learning environments rich in physical stimulation, active behavior models for children, and ongoing observers of gross motor development. In the technological era, teachers are required to integrate technology wisely without reducing children’s need to move and engage in physical activities. However, the implementation of this role faces several challenges, including increased gadget use in children’s daily lives, limited parental support and understanding, insufficient facilities and infrastructure to support physical activities, and the lack of professional training for teachers. The study concludes that close collaboration among teachers, schools, and parents is key to ensuring that children’s gross motor stimulation develops optimally amid technological advancement, and emphasizes the need for policies and support programs oriented toward strengthening physical learning in PAUD institutions.